Spanish Popular Comedy as a Social Reflection: From Tardofrancoism until Today. Radiograph of an era - Pérez Morán, Ernesto (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2014)
Historically, popular comedy has been seen as an understudied entertainment genre, because of its poor quality and apparent playfulness. Movies starring Manolo Escobar, Paco Martínez Soria and Andrés Pajares and Fernando Esteso earned the public’s favor. This did not correspond with the analyst’s minimum interest, and it is something that has been currently happening as in the case the box-office hit Torrente. This collection of movies is the heir to the comedies of the latter years of the Franco Regime and those filmed during Spanish Transition. In this paper, we propose a detailed study of the aforementioned films, shuffling the hypothesis of their strength as an ideological vehicle. We analyze thematic, narrative and aesthetic constant elements to establish the relevance of these works as a palimpsest of half a century of Spanish history